2020
DOI: 10.1002/bmc.4792
|View full text |Cite
|
Sign up to set email alerts
|

Urine metabolomics study of Bushen Huoxue Prescription on diabetic retinopathy rats by UPLC–Q‐exactive Orbitrap–MS

Abstract: Diabetic retinopathy (DR) is a common microvascular complication of diabetes and remains one of the leading causes of blindness worldwide. Previous studies have shown that Bushen Huoxue Prescription (BP) possesses an effect on preventing and treating DR, but the mechanisms of action are not entirely clear. In order to clarify the mechanisms, the pharmacodynamical assessments of BP were investigated. Combining the pharmacodynamical studies, it was found that BP could inhibit high expression of VEGF and HIF‐1α, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Based on the negative impact on the progression of DM and DR, urine metabolomic analysis in diabetic-model Goto-Kakizaki rats showed that metabolites changed by exposure to free CML were matched to carbohydrate metabolism, amino acid metabolism, and the tricarboxylic acid (TCA) cycle ( 90 ). Meanwhile, urine metabolomic research based on UPLC-Q-Exactive Orbitrap-MS was built to explore the metabolic alterations of DR rats and evaluate the therapeutic action of BP on DR, and nine possible biomarkers related to DR were significantly correlated to tryptophan metabolism, lipid metabolism, and gut microbial metabolism in this study ( 91 ).…”
Section: Metabolomics In Diabetic Retinopathymentioning
confidence: 99%
“…Based on the negative impact on the progression of DM and DR, urine metabolomic analysis in diabetic-model Goto-Kakizaki rats showed that metabolites changed by exposure to free CML were matched to carbohydrate metabolism, amino acid metabolism, and the tricarboxylic acid (TCA) cycle ( 90 ). Meanwhile, urine metabolomic research based on UPLC-Q-Exactive Orbitrap-MS was built to explore the metabolic alterations of DR rats and evaluate the therapeutic action of BP on DR, and nine possible biomarkers related to DR were significantly correlated to tryptophan metabolism, lipid metabolism, and gut microbial metabolism in this study ( 91 ).…”
Section: Metabolomics In Diabetic Retinopathymentioning
confidence: 99%
“…The imbalance of tryptophan metabolism has a serious effect on DR and reduces the integrity of the retinal neuron unit. Tryptophan is a potential marker of DR progression in T2D patients ( Yun et al, 2020 ) and DR is mainly associated with tryptophan metabolism ( Wang X. et al, 2020 ). Abnormal levels of tryptophan are highly correlated with T2DM and its complications ( Gong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bushen Huoxue Prescription (BP), comprising Salviae Miltiorrhizae Radix et Rhizoma, Rehmanniae Radix, Puerariae Lobatae Radix, and Ginseng Radix et Rhizoma, has shown promise in DR prevention and treatment. Using urine metabolomics, BP’s anti-DR effect was linked to nine small-molecule metabolites, indicating its potential to regulate gut microbial metabolism, lipid metabolism, and tryptophan metabolism in treating DR. 93 These findings underscore the need for more research to elucidate the molecular effects of TCM on DR’s physiological changes.…”
Section: Metabolomics Studies Of Tcm Treating Diabetic Complicationsmentioning
confidence: 96%